2013
DOI: 10.1007/s00894-013-1901-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical properties of Cu-doping and Zn vacancy impurities in ZnTe

Abstract: The geometric structures of perfect ZnTe, that with Zn vacancy (Zn0.875Te), and Cu-doped ZnTe (Zn0.875Cu0.125Te) were optimized using the pseudopotential plane wave (PP-PW) method based on the density functional theory (DFT) within generalized gradient approximation (GGA). The cohesive energy, band structure, density of states, and Mulliken populations were calculated and discussed in detail. On the other hand, an accurate calculation of linear optical functions (the dielectric function, refraction index, refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For each alloy and any energy less than the first peak energy, there is no loss of electron energy. For x = 0, 0.25, 0.5, 0.75, and 1.0, the energies associated with the Plasmon frequencies are found to be greater than those cited in the work of Gang Wang et al, [37] in the case of Hg 1−x Cd x Te, and in the work of Qing-Fang Li et al, [38] for the ZnTe material. It should be reminded that, in these studies, the computation of the dielectric func-tion was done for gap energies smaller than those used in our work.…”
Section: Optical Propertiesmentioning
confidence: 56%
“…For each alloy and any energy less than the first peak energy, there is no loss of electron energy. For x = 0, 0.25, 0.5, 0.75, and 1.0, the energies associated with the Plasmon frequencies are found to be greater than those cited in the work of Gang Wang et al, [37] in the case of Hg 1−x Cd x Te, and in the work of Qing-Fang Li et al, [38] for the ZnTe material. It should be reminded that, in these studies, the computation of the dielectric func-tion was done for gap energies smaller than those used in our work.…”
Section: Optical Propertiesmentioning
confidence: 56%
“…S. Chandra et al [3] studied the crack growth behavior in the aluminum with vacancies using molecular dynamics simulation method, the results showed that the stress concentration at the crack tip was changed because of the atomic vacancy defects, with the increase of atomic vacancy defects, the crack tip became blunt. Guo Lei et al [4] used first-principle method to study the stability of Zn Vacancy in ZnSe, the result showed that single Zn vacancy defect structure was not easy to form because it was unstable in ZnSe. Xu Zhongfei [5] studied the defect formation energy of double Al or double Cu vacancy defects in AlCu3 structure with first-principles method, the results showed that double Cu vacancy defect was easier to form than double Al vacancy defect.…”
Section: Introductionmentioning
confidence: 99%